Mary Jane Meiklejon, c. 1900 (1900)
1900 "Mary Jane Meiklejon, c. 1900" [t0537.jpg], 1900 Mary Jane Meiklejon was the sister of Robert Noonan (Tressell) and he and his daughter stayed for a while in her Hastings home on their return from South Africa in 1901. When Robert Noonan left Hastings for Liverpool in 1910, in order to make arrangements for their emigration to Canada, Kathleen lived and worked at Mary Meiklejon's special school for blind and mentally handicapped children - the only one in England at the time. In 1914, Kathleen emigrated to Canada and married there Mary's son, Paul Meiklejon.